2018
DOI: 10.1515/jpm-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

The misoprostol vaginal insert compared with oral misoprostol for labor induction in term pregnancies: a pair-matched case-control study

Abstract: The MVI compared with OM significantly shortened the time from application to delivery at the expense of a higher cesarean section rate and negative effects on neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 14 publications
5
30
2
4
Order By: Relevance
“…Uterine hyperstimulation is a drawback of a too efficient induction method. The incidence of uterine hyperstimulation has been found to be more common with MVI than dinoprostone, vaginal misoprostol tablets or OM . Supporting these findings, we found the use of tocolysis to be more common in the MVI group.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Uterine hyperstimulation is a drawback of a too efficient induction method. The incidence of uterine hyperstimulation has been found to be more common with MVI than dinoprostone, vaginal misoprostol tablets or OM . Supporting these findings, we found the use of tocolysis to be more common in the MVI group.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, MVI has been shown to shorten the time interval to vaginal delivery by 6‐14 hours when compared with vaginal dinoprostone, vaginal misoprostol and OM . In our study the time interval difference was even larger.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In many countries MVI is the only misoprostol product approved for induction of labor in women, using evidence from a large randomized controlled trial conducted in the United States [6, 7]. Compared with dinoprostone (prostaglandin E2, PGE2), misoprostol has shown enhanced uterine contractility effects [79], which offer advantages in terms of shorter time interval to delivery but also increases the risk for uterine tachysystole [7, 10, 11].…”
Section: Introductionmentioning
confidence: 99%